Research progress of UV-curable polyurethane acrylate-based hardening coatings - Fu, Junchao; Wang, Li; Yu, Haojie; Haroon, Muhammad; Haq, Fazal; Shi, Wenlei; Wu, Bin; Wang, Libo (Progress in organic coatings, 2019)
With the development of society, plastics play a significant role in daily supplies owing to their advantages. Whereas, insufficient scratch resistance and vulnerable plastic surfaces result in the constraint of their range of application fields, for instance, electronic products. Hence, it is a highly desirable objective of researchers to investigate hardening coatings for protecting plastic surfaces, by selecting polyurethane acrylate (PUA) as film-forming materials attributing to their adjustable features. This article reveals components of PUA and principles for its hardening modification, and summaries various methods of hardening modification of PUA-based coatings, such as improving the crosslinking density, strengthening hydrogen bonding, incorporating rigid groups into molecular structure, introducing inorganic nanoparticles into resin matrix and transferring linear PUA into hyperbranched analogs. Moreover, optimal strategies for the preparation of PUA-based hardening films from above five tactics are discussed.